Yes, Managers Should Be Paid Like Bureaucrats - Bruno S. Frey; Margit Osterloh (Center for Research in Economics, Management and the Arts (CREMA), 2004)
Corporate scandals, reflected in excessive management compensation and fraudulent accounts, cause considerable damage. Agency theory's insistence on linking the compensation of managers and directors as closely as possible to firm performance is a major reason for these scandals. They cannot be overcome by improving variable pay for performance, as selfish extrinsic motivation is reinforced. Based on the common pool approach to the firm, institutions are proposed which serve to raise intrinsically motivated corporate virtue. More importance is to be attributed to fixed pay and strengthening the legitimacy of authorities by procedural fairness, relational contracts and organizational citizenship behavior.
Keywords: D21; D23; J33; L20; 330; Agency theory; intrinsic motivation; crowding theory; management compensation pay for performance; organizational citizenship